The global interior : mineral frontiers and American power - Black, Megan, 1987- (Harvard University Press, 2018)
In the twentieth century, the innermost arm of the American state, the US Department of the Interior pursued minerals beyond US borders, spanning continents, plumbing depths, and reaching into the heavens. Although the Interior Department is known today for managing natural resources and indigenous peoples in a domestic context, it has long facilitated US expansion. Founded in the mid-nineteenth century to oversee settler colonialism, the Interior Department faced obsolescence with the close of the frontier in the 1890s. As consequence, Interior leaders redirected a skillset of expansion toward natural resource management, increasingly targeting minerals indispensable to industrial society. Facing limits to domestic reserves, Interior sought mineral frontiers across the world--in overseas territories, Third World nations, the continental shelf, and even outer space. The environment became, for Interior and the nation, a means and logic of US intervention. Bridging the fields of US foreign relations history, environmental history, and political economy, The Global Interior ultimately argues that the Interior Department was a key mechanism for ensuring and obscuring an ongoing American project of global extraction.--